1993
DOI: 10.1128/mcb.13.12.7961
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cDNAs encoding the Drosophila GAGA transcription factor.

Abstract: To investigate the mechanisms involved in expression of the Drosophila melanogaster engrailed gene, we purified GAGA protein, one of several putative transcriptional activator proteins that binds to the proximal region of the engrailed promoter. Antibodies raised against GAGA protein were used to demonstrate that the protein is present in all nuclei of young embryos. We isolated cDNA clones encoding GAGA protein in which a putative 519-codon open reading frame contains general sequence motifs characteristic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
2
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 50 publications
10
145
2
4
Order By: Relevance
“…1b). A footprinting analysis indicated that they are binding sites for non-RNA-polymerase II proteins, most probably GAGA factors involved in transcriptional activation in cultured cells (Soeller et al 1988(Soeller et al , 1993; there is no evidence for GAGA factor binding to the fourth CTCTC at À36/±32. The ®rst three CTCTCs are surrounded or associated with CX (X an arbitrary base) or GX repeats, and these repeats represent about 50% of the sequence upstream of RNA starts of D-168 (for the en sequence, see Kassis et al 1989).…”
Section: Gaga Repeat As a Functional Substitute For En Upstream Promomentioning
confidence: 93%
“…1b). A footprinting analysis indicated that they are binding sites for non-RNA-polymerase II proteins, most probably GAGA factors involved in transcriptional activation in cultured cells (Soeller et al 1988(Soeller et al , 1993; there is no evidence for GAGA factor binding to the fourth CTCTC at À36/±32. The ®rst three CTCTCs are surrounded or associated with CX (X an arbitrary base) or GX repeats, and these repeats represent about 50% of the sequence upstream of RNA starts of D-168 (for the en sequence, see Kassis et al 1989).…”
Section: Gaga Repeat As a Functional Substitute For En Upstream Promomentioning
confidence: 93%
“…and C.w., manuscript in preparation). POlyclonal antibodies against GAGA were prepared in rabbits from protein expressed in E. cofi 10 and purified to >95% homogeneity on heparin-Sepharose CL6B and by preparative SDS-PAGE. Preimmune and immune sera (5 111 -100 +1 +100…”
Section: Pre-immunementioning
confidence: 99%
“…Four genes we show to be dependent on nurf301 for expression-Ubx, en, hsp26, and hsp70-all contain multiple binding sites for the GAGA factor, which is genetically required for their correct expression (Soeller et al 1993;Farkas et al 1994;Bhat et al 1996). On the Drosophila hsp70 and hsp26 promoters (GA.CT) n cognate elements to which the GAGA factor binds are required for HSF-binding.…”
Section: Nurf Is Required For Transcription In Vivomentioning
confidence: 99%